The Routledge handbook of gender and violence - Lombard, Nancy (Routledge, 2018)
The Routledge Handbook of Gender and Violence provides both a comprehensive and authoritative state-of-the-art overview of the latest research in the field of gender and violence. Each of the 23 specially commissioned chapters develops and summarises their key issue or debate including rape, stalking, online harassment, domestic abuse, FGM, trafficking and prostitution in relation to gender and violence. They study violence against women, but also look at male victims and perpetrators as well as gay, lesbian and transgender violence. The interdisciplinary nature of the subject area is highlighted, with authors spanning criminology, social policy, sociology, geography, health, media and law, alongside activists and members of statutory and third sector organisations. The diversity of perspectives all highlight that gendered violence is both an age-old and continuing social problem. By drawing together leading scholars this handbook provides an up-to-the-minute snapshot of current scholarship as well as signposting several fruitful avenues for future research. This book is both an invaluable resource for scholars and an indispensable teaching tool for use in the classroom and will be os interest to students, academics, social workers and other professionals working to end gender-based violence.
Keywords: approches et analyses; communication; cours; criminologie; discipline; droit; géographie; justice sociale; outils; ouvrages de références; premier cycle; rapports sociaux de sexe; ressource en ligne; santé; science politique et droit; sciences humaines; sex1911; sexualité; sociologie; sofia; thématiques; travail; violences

Encyclopédie critique du genre: corps, sexualité, rapports sociaux - Rennes, Juliette (La Découverte, 2016)
""Désir(s)", "Mondialisation", "Nudité", "Race", "Voix"... Les soixante-six textes thématiques de cette encyclopédie explorent les reconfigurations en cours des études de genre. Trois axes transversaux organisent cette enquête collective: le corps, la sexualité, les rapports sociaux. Dans les activités familiales, sportives, professionnelles, artistiques ou religieuses, les usages du corps constituent désormais un terrain privilégié pour appréhender les normes et les rapports de genre. Les pratiques érotiques que les sociétés, à travers l'histoire, ont catégorisées comme normales ou déviantes occupent quant à elles une place inédite pour éclairer les articulations entre hiérarchies des sexes et des sexualités. Enfin, les inégalités liées au genre sont de plus en plus envisagées en relation avec celles liées à la classe sociale, la couleur de peau, l'apparence physique, la santé ou encore l'âge. Cette approche multidimensionnelle des rapports sociaux a transformé radicalement les manières de penser la domination au sein des recherches sur le genre. En analysant les concepts, les enquêtes empiriques et les débats caractéristiques de ces transformations saillantes, les contributrices et contributeurs de cet ouvrage dessinent une cartographie critique des études de genre en ce début de XXIe siècle."–Page 4 de la couverture.
Keywords: LGBTQIA2+; approches et analyses; corps; cours; famille; har4600; identités LGBTQIA2+; intersectionnalité; outils; ouvrages de références; premier cycle; queer; rapports sociaux de sexe; sexualité; thématiques

The SAGE handbook of feminist theory - Evans, Mary (SAGE reference, 2014)
At no point in recorded history has there been an absence of intense, and heated, discussion about the subject of how to conduct relations between women and men. This Handbook provides a comprehensive guide to these omnipresent issues and debates, mapping the present and future of thinking about feminist theory. The chapters gathered here present the state of the art in scholarship in the field, covering: Epistemology and marginality; Literary, visual and cultural representations; Sexuality; Macro and microeconomics of gender; Conflict and peace. The most important consensus in this volume is that a central organizing tenet of feminism is its willingness to examine the ways in which gender and relations between women and men have been (and are) organized. The authors bring a shared commitment to the critical appraisal of gender relations, as well as a recognition that to think ‘theoretically’ is not to detach concerns from lived experience but to extend the possibilities of understanding. With this focus on theory and theorizing about the world in which we live, this Handbook asks us, across all disciplines and situations, to abandon our taken-for-granted assumptions about the world and interrogate both the origin and the implications of our ideas about gender relations and feminism. It is an essential reference work for advanced students and academics not only of feminist theory, but of gender and sexuality across the humanities and social sciences.
Le chapitre Boyle, K. (2014). Feminism and pornography (pp. 215-231) a été donné en lecture au cours SEX1911.
Keywords: approches et analyses; corps; cours; discipline; har4600; histoire et politique; intersectionnalité; outils; ouvrages de références; philosophie; phénoménologie; premier cycle; rapports sociaux de sexe; ressource en ligne; sciences de la gestion; sciences humaines; sciences sociales; sex1911; thématiques; violences; économie; épistémologie; études féministes